CASTOR BEAN CAKE IN TOP-DRESSING APPLICATION AS A SOURCE OF NITROGEN ON THE PRODUCTION AND QUALITY OF ZUCCHINI ORGANIC SEEDS - Lima Lanna, Natalia de Brito [UNESP]; Bardiviesso, Estefania Martins [UNESP]; Barbosa Tavares, Ana Emilia; Lima Silva, Priscilla Nataly de [UNESP]; Nakada-Freitas, Pamela Gomes [UNESP]; Hara Noda, Sayuri Beatriz [UNESP]; Inacio Cardoso, Antonio Ismael [UNESP] (Univ Federal Uberlandia, 2020)
Studies in vegetables show that fertilization influences seed production positively, however, when the quality of the seeds is analyzed, the results are mostly inconsistent. The objective of this study was to evaluate the effect of castor bean cake (CBC) dose splitting in top-dressing application on the production and quality of zucchini organic seeds, as well as its effect on the macronutrient content of fruits and seeds. The experimental design was a randomized block design and four replications. There were 13 treatments with four doses of CBC in top-dressing (1.7, 3.4, 5.1 and 6.8 t ha-1) per three applications (33.3-33.3-33.3%, 50-50% and 33-50-17%) and the control treatment without any kind of top-dressing fertilization. The study evaluated the number of ripe fruits per plant, the production (number and mass) of seeds per fruit and per plant, the mass of one hundred seeds, seed germination, first germination count, and macronutrient content in the diagnosis leaf, in mature fruits (without seeds) and seeds. The number of ripe fruits per plant was not affected by the CBC doses in top-dressing, neither by the splitting of the applications. It was observed that the number of seeds per fruit, mass of seeds per fruit and mass of seeds per plant showed quadratic behavior. Regarding seed quality, only the 1.7; 3.4 and 5.1 t ha(-1) doses produced seed with superior quality than the other doses. In conclusion, the CBC doses increased the number of seeds per fruit, mass of seeds per fruit and per plant up to the 4.5t ha(-1) dose, approximately.
Keywords: Cucurbita pepo; Germination; Nitrogen fertilization; Organic fertilization; Vigor